Analisis Persediaan Bahan Baku Kedelai Dengan Metode Economic Order Quantity Pada Pabrik Tahu Jawa Pak Udin - Arfadila, Dwi; Banjarnahor, Haposan (Prosiding, 2024)
Indonesia has now entered the ASEAN economic era which requires companies to maximize profits through cost efficiency and good management. Inventory management is crucial in the manufacturing industry to optimize production and maintain timely availability of raw materials. This research aims to conduct an in-depth analysis of the inventory management of soybean raw materials using the Economic Order Quantity (EOQ) method at Pak Udin's Javanese Tofu Factory in Batam City. The aim is to identify the most efficient way to manage soybean inventories, by minimizing total inventory costs and ensuring optimal availability of raw materials for the continuity of factory operations. This research adopts a qualitative approach with descriptive methods. Data was collected through interviews with Mr. Udin as the factory owner, direct observation at the factory location, and analysis of related documents such as production reports, raw material purchase data, and storage costs. Case study techniques are used to gain an in-depth understanding of existing inventory management practices. Implementation of the EOQ method at the Javanese Tofu Factory has resulted in significant cost savings in soybean inventory management. By using EOQ, factories can determine the optimal order quantity based on ordering costs, carrying costs, and stable demand from the market. Implementation of EOQ also helps in maintaining adequate inventory levels and avoids additional costs due to excess or shortage of inventory. Pak Udin's Javanese Tofu Factory faces several challenges in managing soybean supplies, such as fluctuations in raw material prices and variations in market demand.